Molecular basis for AUXIN RESPONSE FACTOR protein interaction and the control of auxin response repression - Korasick, David A. (National Academy of Sciences, 2014)
In plants, the AUXIN RESPONSE FACTOR (ARF) transcription factor family regulates gene expression in response to auxin. In the absence of auxin, ARF transcription factors are repressed by interaction with AUXIN/INDOLE 3-ACETIC ACID (Aux/IAA) proteins. Although the C termini of ARF and Aux/IAA proteins facilitate their homo- and heterooligomerization, the molecular basis for this interaction remained undefined. The crystal structure of the C-terminal interaction domain of Arabidopsis ARF7 reveals a Phox and Bem1p (PB1) domain that provides both positive and negative electrostatic interfaces for directional protein interaction. Mutation of interface residues in the ARF7 PB1 domain yields monomeric protein and abolishes interaction with both itself and IAA17. Expression of a stabilized Aux/IAA protein (i.e., IAA16) bearing PB1 mutations in Arabidopsis suggests a multimerization requirement for ARF protein repression, leading to a refined auxin-signaling model.